CITRA DESTINASI DAN PRODUK WISATA BERPENGARUH TERHADAP KEPUASAN DAN LOYALITAS PENGUNJUNG PANTAI SLOPENG DI KABUPATEN SUMENEP - Humairoh, Tuffahul; Andriani, Nurita (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Slopeng Beach is an ideal place to unwind and enjoy the view. On the other hand, Slopeng Beach has received a lot of bad feedback from visitors. This study aims to analyse the relationship effects of destination image, tourism products, visitor satisfaction and destination loyalty of Slopeng Beach in Sumenep District. A quantitative strategy was used in the study, which involved the use of a survey instrument called a questionnaire. Using the SmartPLS (partial least squares) approach, regression analysis and Structura lEquation Model (SEM) were used for analysis. The results of this study reveal that destination image has a positive effect on visitor satisfaction, tourism products show a positive effect on satisfaction, visitor satisfaction variables have a positive effect on loyalty, Destination Image has a positive effect on Loyalty, and Tourism Products have an insignificant negative effect on Loyalty. In addition, destination image and tourism products have an influence on loyalty through visitor satisfaction.